A systematic and comparative study on the line-changing strategies in top-level table tennis players - Guo, W.; Liang, M.; Xiao, D.; Hao, W. (International Journal of Performance Analysis in Sport, 2020)
Line-changing strategies are key tactics that can contribute to the successful performance of table tennis players. The purposes of this study were to explore the characters and development trend of line-changing tactics in top-level table tennis players and compare the differences of line-changing tactics between Chinese players and players from other countries. A computerised notational analysis was performed by using the specialised technical and tactical video analysis system of "Ping Pong Military Division" with 80 table tennis matches played by 24 right-hand male top-ranked players as samples and chose the usage rate, scoring rate and contribution rate as the evaluation parameters of different line-changing tactics. The results showed that (1) the line-changing strategies were more widely used in the new plastic ball era, and the tactic of changing the line to forehand position and changing the line from crosscourt to crosscourt tactics increased significantly; (2) Chinese players had outstanding scoring skills in line-changing strategies, not only for the consciousness but also for the scoring ability. These ?ndings indicated that stroke placement and stroke line are playing an increasingly important role in table tennis, which may inform coaches and players for taking corresponding countermeasures.